Complexity of gauge bounded Cartier algebras. Issue 8 (2nd August 2020) - July, Henry; Stäbler, Axel
Abstract: We show that a gauge bounded Cartier algebra has finite complexity. We also give an example showing that the converse does not hold in general. Communicated by Graham J. Leuschke